The Concept of α-Synuclein Strains and How Different Conformations May Explain Distinct Neurodegenerative Disorders - Malfertheiner, Katja; Stefanova, Nadia; Heras-Garvin, Antonio (Frontiers in Neurology, 2021)
In the past few years, an increasing amount of studies primarily based on experimental models have investigated the existence of distinct α-synuclein strains and their different pathological effects. This novel concept could shed light on the heterogeneous nature of α-synucleinopathies, a group of disorders that includes Parkinson's disease, dementia with Lewy bodies and multiple system atrophy, which share as their key-molecular hallmark the abnormal aggregation of α-synuclein, a process that seems pivotal in disease pathogenesis according to experimental observations. However, the etiology of α-synucleinopathies and the initial events leading to the formation of α-synuclein aggregates remains elusive. Hence, the hypothesis that structurally distinct fibrillary assemblies of α-synuclein could have a causative role in the different disease phenotypes and explain, at least to some extent, their specific neurodegenerative, disease progression, and clinical presentation patterns is very appealing. Moreover, the presence of different α-synuclein strains might represent a potential biomarker for the diagnosis of these neurodegenerative disorders. In this regard, the recent use of super resolution techniques and protein aggregation assays has offered the possibility, on the one hand, to elucidate the conformation of α-synuclein pathogenic strains and, on the other hand, to cyclically amplify to detectable levels low amounts of α-synuclein strains in blood, cerebrospinal fluid and peripheral tissue from patients. Thus, the inclusion of these techniques could facilitate the differentiation between α-synucleinopathies, even at early stages, which is crucial for successful therapeutic intervention. This mini-review summarizes the current knowledge on α-synuclein strains and discusses its possible applications and potential benefits.